PENGARUH KETERLIBATAN KERJA, LOCUS OF CONTROL DAN GAYA KEPEMIMPINAN TERHADAP HUBUNGAN ANTARA PARTISIPASI PENYUSUNAN ANGGARAN DENGAN KINERJA MANAJERIAL (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2005)
The relationship between budget participation and managerial performance which has been studied in several research in accounting has achieved inconsistent result. One of the way to reconcile these inconsistencies is to study the problem using contingency approach (Govindarajan, 1986). This research endeavors to find a solution to this inconsistencies by applying contingency approach. Three contingency variables are studied here, that is work involvement, locus of control, and leadership style. Questionnaire is sent to 290 manufacturing companies in East Java, resulting in responses from 56 managers (19,3%) which are then submitted into regression analysis. This study shows that, first, the result of the analysis reject the hypothesis that interaction between work involvement and budget participation affects managerial performance. Second, the result of the analysis confirms that threre exists an interactional effect of locus of control and budget participation toward managerial performance. Third, the result of the analysis reject the hypothesis that the effect of budget particiption toward performance is hight for consideration leadership style, which is consistence with the result from Safriliana (2001) and the result of the analysis also reject the hypothesis that the effect of budget participation toward managerial performance is low for initiative leadership style. The latter finding is also consistent with the result from Safriliana (2001).